A New Approach to Mix Design of Green Concrete Using Slag - MALALLAH, Mohammad Abdul-Kareem; DAWOOD, Eethar Thanon (Engineering Transactions, 2025)
A new method for designing the mix proportions of green concrete using slag has been proposed. The approach includes three different mixes: the first mix (1 : 2.62 : 4.87) used 275 kg/m3 of cement, the second mix (1 : 2.38 : 4.42) used 300 kg/m3 of cement, and the third mix (1 : 1.99 : 3.7) used 350 kg/m3 of cement. The green concrete mixes for these groups were produced with 35%, 40%, and 45% slag powder as partial replacement for the weight of cement. The results showed that the compressive strength of green concrete at 28 days for 35% substitution was approximately similar to that of the reference concrete. However, for 40% and 45% replacements, the compressive strength was reduced by 9.4% and 20.4%, respectively. Additionally, the CO2 emission and costs associated with producing 1 m3 of reference and green concrete were considered in this study. The incorporation of 35%, 40%, and 45% slag powder as a cement substitution reduced CO2 emissions by 24.7%, 28.7%, and 33.1%, and production costs by 16%, 16.8%, and 17.4%, respectively, compared to reference concrete. The suggested mix design approach for green concrete was developed using seven equations for preparing the mix proportion. Most of the equations achieved an R2 of about 0.9, except for the equation determining binder content, which had an R2 of about 0.8. The suggested approach depends on the compressive strength, slump, and superplasticizer dosage. The results show the ability of the proposed approach to achieve compressive strength higher than the design compressive strength.